Analisis Koordinasi Dinas Sosial dalam Pelaksanaan Program Bantuan Sosial Tunai di Kelurahan Wonokusumo Kecamatan Semampir Kota Surabaya - Intan Priska Wardani; Sasmito Jati Utama (Faculty of Social and Political Science, 2022)
The Cash Social Assistance (BST) is an assistance program from the Ministry of Social Affairs of the Republic of Indonesia which is given to vulnerable and poor communities affected by the COVID-19 pandemic. The purpose of this study was to analyze in depth the coordination of government agencies in Wonokusumo Village, Semampir District, Surabaya City. This study uses the theory of James D. Thompson 3 types of coordination (unified interdependence, sequential interdependence, reciprocal interdependence) with aspects of identification of the parties involved and participating as well as the availability of implementation instructions and technical guidelines. The study used a qualitative descriptive approach. The results of this study indicate that the coordination of the parties involved from PT. Pos Indonesia, Social Service, Subdistrict, Kelurahan, RT/RW seen from these 3 aspects the coordination of the implementation of cash social assistance programs in Wonokusumo Village, Semampir District, Surabaya City has been going well according to the specified standard procedure. as for supporting factors such as responsive agency resources as well as optimal community involvement for the inhibiting factor in this study, the quantity of village resources is proportional to the large number of local residents. The suggestion in this research is to increase the role of Wonokusumo village human resources, namely by holding training according to their fields and also increasing the level of education from D3 to Bachelor as a form of community service.